Stenope, a new euphorine genus from the Philippines (Hymenoptera: Braconidae) - van Achterberg, Cornelis; Ang, Yuchen; Reshchikov, Alexey; Yue, Qi (Zootaxa, 2018)
A new genus (Stenope gen. nov.; type species: Allophrys falcatus) is described for the aberrant type species from the Philippines accidently described as an ichneumonid species.